Gamma delta T cells and uses thereof - LEEK MICHAEL; HANNIGAN ADELE (2017)
A method of preparing and using gamma delta T cells in the allogeneic or autologous treatment of subjects suffering from virus infection, fungal infection, protozoal infection and cancer. 制备γδT细胞和使用其同种异体或自体治疗患有病毒感染、真菌感染、原生动物感染和癌症的受试者的方法。